Surgical Versus Nonsurgical Interventions to Relieve upper Airway Obstruction in Children with Pierre Robin Sequence - Karen Kam; Meghan McKay; Joanna MacLean; Manisha B Witmans; Sheldon Spier; Ian Mitchell (Canadian Respiratory Journal)
BACKGROUND: Newborns with Pierre Robin sequence (PRS) often experience chronic intermittent hypoxemia/hypoventilation associated with airway obstruction. The heterogeneity of the severity of upper airway obstruction makes management a challenge; the optimal intervention in individual cases is not clear.